(untitled) (Transactions on Additive Manufacturing Meets Medicine, 2019)
3D printing is already an important part of the medical treatment and diagnosis of patients today. It is becoming apparent that the importance of 3D printing in the medical environment will gradually increase. In this context, the question arises as to whether the starting point for medical device law is merely the manufacturing of custom-made devices or whether there is a need for further regulation. This approach concerns the software used, the production of medical devices, the use of data as well as the product liability of the manufacturer. With regard to the application of 3D printing not only by traditional industrial companies, but increasingly also by doctors must also be asked to what extent doctors take product responsibility. The current medical device law cannot reflect these developments alone. The options and limitations of 3D printing must be reflected in various laws (Medical Device Law, Product Liability Law, Data Protection Laws, etc.) as well as technical and medical standards in order to ensure adequate safety and protection for patients. This also applies to the testing and research of 3D printing and prototypes in humans. .